2016
DOI: 10.1002/2016wr019303
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dynamics in the hyporheic zone of a headwater mountain stream in the Cascade Mountains, Oregon

Abstract: We investigated carbon dynamics in the hyporheic zone of a steep, forested, headwater catchment western Oregon, USA. Water samples were collected monthly from the stream and a well network during base flow periods. We examined the potential for mixing of different source waters to explain concentrations of DOC and DIC. We did not find convincing evidence that either inputs of deep groundwater or lateral inputs of shallow soil water influenced carbon dynamics. Rather, carbon dynamics appeared to be controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…This indicated that downwelling can affect the growth of invertebrate communities by removing organic matter from the river, which controls their metabolism. This finding is supported by the literature on carbon cycling [77,83]. Chironomidae were dependent on HCO 3 − (Figure 3c), hence, their demand for organic matter was more pronounced.…”
Section: Effect Of Downwelling Dynamics On Macroinvertebrate Communitiessupporting
confidence: 87%
“…This indicated that downwelling can affect the growth of invertebrate communities by removing organic matter from the river, which controls their metabolism. This finding is supported by the literature on carbon cycling [77,83]. Chironomidae were dependent on HCO 3 − (Figure 3c), hence, their demand for organic matter was more pronounced.…”
Section: Effect Of Downwelling Dynamics On Macroinvertebrate Communitiessupporting
confidence: 87%
“…Similar to other detrital-based, heterotrophic streams, low nitrogen and phosphorus concentrations at our study site could limit metabolic activity [120]. The bioavailability of these nutrients likely limit microbial metabolism in our system under all flow conditions [116,121,122]. However, we would expect these limitations to be minimized along shallow, intermittently inundated, and hydrologically youngest flowpaths that experience warmer temperatures, are nearer to light exposure, increased reactive surface area, and availability of fresh organic matter sources.…”
Section: Older Storage Is Not As Metabolically Active As Younger Storagementioning
confidence: 81%
“…Lastly, metabolic activity may be energetically constrained on timescales relevant to the water residence time along these longer and hydrologically older flowpaths. Previous work has suggested that buried particulate organic matter from debris flows promotes hyporheic microbial respiration at the study site [122]. While this buried organic matter, likely western hemlock (Tsuga heterophylla) and Douglas fir (Pseudotsuga menziesii) wood and needles, may persistently increase metabolic activity of the oldest water at the site, it is also likely a low-quality organic matter source with less reaction potential, relative to the younger organic matter along the shallower hyporheic flowpaths, given its composition and old age within the stream corridor [123].…”
Section: Older Storage Is Not As Metabolically Active As Younger Storagementioning
confidence: 91%
“…See Table and supporting information Figure S1 for uniform and spatially variable groundwater inflow velocities during the high, medium, and low stream discharge conditions. Stream discharge and UAA estimates are consistent with recent work done in the catchment [ Corson‐Rikert et al ., ].…”
Section: Methodsmentioning
confidence: 97%